The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s0034-737x2014000300011
|View full text |Cite
|
Sign up to set email alerts
|

Relações entre caracteres de tubérculo de batata nas primeiras gerações de seleção

Abstract: Relationships among potato tuber traits in early generations of selectionThe objective of this study was to evaluate the relationships among tuber traits in potato progenies in the seedling generation and in the first clonal generation. The experiments were carried out at Embrapa Clima Temperado, in Pelotas, RS. Twelve potato progenies were grown as seedling generation in a greenhouse in the crop year 2010/2011 and the first field generation was grown in the crop year 2011/2012. The two trials were arranged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
1
1
0
1
Order By: Relevance
“…The authors Pinto et al (2010) and Silva et al (2016), when verifying the productive potential of cultivar Asterix in six and two environments, respectively, observed its inferior performance in relation to several clones tested, such results corroborate with those obtained in this study according to Silva et al (2014), this is probably due to the problems of adaptation of foreign cultivars to the edaphoclimatic conditions of Brazil. Similarly Souza et al (2007) found large differences in the performance of genotypes evaluated in different environments, thus demonstrating that genotype-environment interaction is important in potato crop.…”
Section: Generalsupporting
confidence: 83%
See 1 more Smart Citation
“…The authors Pinto et al (2010) and Silva et al (2016), when verifying the productive potential of cultivar Asterix in six and two environments, respectively, observed its inferior performance in relation to several clones tested, such results corroborate with those obtained in this study according to Silva et al (2014), this is probably due to the problems of adaptation of foreign cultivars to the edaphoclimatic conditions of Brazil. Similarly Souza et al (2007) found large differences in the performance of genotypes evaluated in different environments, thus demonstrating that genotype-environment interaction is important in potato crop.…”
Section: Generalsupporting
confidence: 83%
“…The traits analyzed were: total tuber mass (TTM: kg.parcel -1 ), mass of commercial tubers (MCT: kg.parcel -1 ), mean tuber mass (obtained by dividing the total mass of the plot by the total number of tubers -MTM: g.tuber -1 ), percentage of the commercial tuber mass (obtained by dividing the mass of commercial tubers by the total mass of tubers, multiplied by 100 -PCM: %), secondary growth (GRO: %), greening (GRE: %), cracking (CRA: %), sprouting (SPR: %) ( Figure 2A, 2B, 2C and 2D, respectively), dry mass (DM: %) (AOAC,1995), content of reducing sugars was quantified based on glucose (GLUC: mg.g -1 fresh mass) (Silva, 2019). To evaluate the external appearance characters of tubers, a ninepoint grading scale (Silva et al, 2014) was used for: film texture (TEX: Figure 2E), tuber shape uniformity (SHU), tuber size uniformity (SIU), tuber pointing ( Figure 2F), tuber curvature (CUR), overall tuber appearance (APP) and tuber shape (SHA). The data obtained were submitted to deviance analysis at 5% probability by the chisquare test (X²).…”
Section: Methodsmentioning
confidence: 99%
“…Dentre essas características, grande importância é dada ao rendimento de tubérculos, objetivando maior rentabilidade para os produtores e diluição dos custos de produção, contribuindo para a sustentabilidade financeira do cultivo. O desafio de atender a essas exigências requer boa eficiência dos programas de melhoramento na identificação de genótipos superiores para serem registrados como novas cultivares (ESCHEMBACK et al, 2014;SILVA et al, 2014). Em relação ao rendimento de tubérculos, sabe-se que plantas que produzem elevado número de tubérculos apresentam, geralmente, tubérculos menores (SILVA et al, 2012), e tanto o número quanto o tamanho dos tubérculos influenciam diretamente o rendimento de tubérculos comerciais (SILVA et al, 2006).…”
Section: Introductionunclassified